APPLYING SECOND LANGUAGE ACQUISITION THEORIES TO ENHANCE SPEAKING SKILLS IN PRIMARY EDUCATION STUDENTS - Juraeva, Mokhira (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2024)
Teaching foreign languages to students of non-philological education based on a comprehensive approach envisages paying special attention to the development of oral speech at all stages of the continuous education system, especially in higher education. Today, the need to prepare students for international and intercultural relations and international cooperation and the need for teacherspedagogues to be regularly informed about the news related to their field makes it essential for students to learn foreign languages, particularly English. In determining the topic and object of this research work, the process of teaching foreign languages in various higher educational institutions of our country was analyzed. Various conferences were attended in the framework of the topic. Based on these sources, the article presents a number of reasons justifying the relevance of our research, including the fact that in the latest decisions of the President of the Republic of Uzbekistan, the emphasis on learning a foreign language has been determined. The content and principles of the comprehensive approach to the consistent organization of the implementation of these tasks were analyzed. The advantages and disadvantages of a comprehensive approach were studied in the development of methodical support for the development of speaking skills of primary education students in learning English.
Keywords: integrative approach; speech competence; speech development; students; primary education; foreign language; complex approach